2008
DOI: 10.1038/nature06760
|View full text |Cite
|
Sign up to set email alerts
|

Super-chondritic Sm/Nd ratios in Mars, the Earth and the Moon

Abstract: Small isotopic differences in the atomic abundance of neodymium-142 (142Nd) in silicate rocks represent the time-averaged effect of decay of formerly live samarium-146 (146Sm) and provide constraints on the timescales and mechanisms by which planetary mantles first differentiated. This chronology, however, assumes that the composition of the total planet is identical to that of primitive undifferentiated meteorites called chondrites. The difference in the 142Nd/144Nd ratio between chondrites and terrestrial sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
163
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 29 publications
7
163
1
4
Order By: Relevance
“…Caro et al (2008) have argued that this is an unlikely possibility. To make this case more convincing, we explore more systematically scenarios whereby the common point for terrestrial planets shown in figure 7 can be explained by an early differentiation event as argued for the Earth by Boyet & Carlson (2005).…”
Section: (B ) the Nd-isotope Composition Of The Terrestrial Planetsmentioning
confidence: 99%
See 4 more Smart Citations
“…Caro et al (2008) have argued that this is an unlikely possibility. To make this case more convincing, we explore more systematically scenarios whereby the common point for terrestrial planets shown in figure 7 can be explained by an early differentiation event as argued for the Earth by Boyet & Carlson (2005).…”
Section: (B ) the Nd-isotope Composition Of The Terrestrial Planetsmentioning
confidence: 99%
“…Thus, one may conclude that the observations of Caro et al (2008) imply that the Sm-Nd fractionation observed in Martian meteorites must have taken place either before or immediately after accretion. However, if one calls upon the segregation of a hidden reservoir, the Sm-Nd fractionation must have been strikingly identical to that observed in the Earth.…”
Section: (B ) the Nd-isotope Composition Of The Terrestrial Planetsmentioning
confidence: 99%
See 3 more Smart Citations